Microorganisms as bio‐filters to mitigate greenhouse gas emissions from high‐altitude permafrost revealed by nanopore‐based metagenomics. Issue 2 (8th May 2022) - Dang, Chenyuan; Wu, Ziqi; Zhang, Miao; Li, Xiang; Sun, Yuqin; Wu, Ren'an; Zheng, Yan; Xia, Yu
Abstract: The distinct climatic and geographical conditions make high‐altitude permafrost on the Tibetan Plateau suffer more severe degradation than polar permafrost. However, the microbial responses associated with greenhouse gas production in thawing permafrost remain obscured. Here we applied nanopore‐based long‐read metagenomics and high‐throughput RNA‐seq to explore microbial functional activities within the freeze‐thaw cycle in the active layers of permafrost at the Qilian Mountain. A bioinformatic framework was established to facilitate phylogenetic and functional annotation of the unassembled nanopore metagenome. By deploying this strategy, 42% more genera could be detected and 58% more genes were annotated to nitrogen and methane cycle. With the aid of such enlarged resolution, we observed vigorous aerobic methane oxidation by Methylomonas, which could serve as a bio‐filter to mitigate CH4 emissions from permafrost. Such filtering effect could be further consolidated by both on‐site gas phase measurement and incubation experiment that CO2 was the major form of carbon released from permafrost. Despite the increased transcriptional activities of aceticlastic methanogenesis pathways in the thawed permafrost active layer, CH4 generated during the thawing process could be effectively consumed by the microbiome. Additionally, the nitrogen metabolism in permafrost tends to be a closed cycle and active N2 O consumption by the topsoil community was detected in the near‐surface gas phase. Our findings reveal that although the increased thawed state facilitated the heterotrophic nitrogen and methane metabolism, effective microbial methane oxidation in the active layer could serve as a bio‐filter to relieve the overall warming potentials of greenhouse gas emitted from thawed permafrost. Abstract : On‐site MinION metagenomics and RNA‐seq were combined to explore microbial functionalities of active layers of the soil of Qilian Mountain permafrost. With the developed annotation pipeline‐FUNpore, 42% more genera and 58% more genes were detected. Active methane consumption by Methylomonas could serve as a biofilter to mitigate CH4 emission from permafrost. Dissimilatory nitrate reduction to ammonia pathway enabled a closed microbial nitrogen cycle and N2 O consumption was observed. Highlights: On‐site MinION metagenomics and RNA‐seq were combined to explore microbial functionalities of active layers of the soil of Qilian Mountain permafrost. With the developed annotation pipeline‐FUNpore, 42% more genera and 58% more genes were detected. Active methane consumption by Methylomonas could serve as a biofilter to mitigate CH4 emission from permafrost. Dissimilatory nitrate reduction to ammonia pathway enabled a closed microbial nitrogen cycle and N2 O consumption was observed.